Preference of learning style among the Diploma students of UiTM Penang : an overview / Cheang Eng Kwong, Mah Boon Yih and Ch'ng Pei Eng - Cheang, Eng Kwong; Mah, Boon Yih; Ch'ng, Pei Eng (Research Management Institute (RMI), 2010)
This paper gives a brief over view of UiTM Penang diploma students preferences of learning styles specifically among those who are undertaking the English language courses. The five types of learning styles - auditory, visual, tactile. group, and individual are examined with the particular objectives of whether gender andthe types of programs taken affect the learning styles of the students. The study also emphasize on the students' results of SPM and UiTM English courses ': whether or not their preferences were affected by their learning styles. Thus, the Chi-square test and reliability test were used to measure the significance and the consistent reliability. The findings Shows that auditory, tactile, and group learning styles were predominantly popular among the students of different gender; programs of study and those who had obtained different grades of their SPM and UiTM examination results. The writers hope that the findings of this study may provide new directions in the teaching of English courses in UiTM.